(untitled) (International Journal of Language, Literacy and Translation, 2025)
The language used in business and economics is characterized by being informative; it can consist of technical and literal language related to metaphorical expressions. The main objective of this study is to examine how translators deal with the translation of modality expressions in business and economics corpus. The sampling used in this research is purposive sampling. Samples are selected from two websites, following Toolan's (2014) classification of modal markers. The findings indicate that both direct and oblique translation procedures were employed by the translators from both websites. However, there were instances of meaning loss observed in the translation of probability markers as well as obligatory markers. Moreover, the due to Arabic language norms, willingness markers are found to occur abstractly in Arabic. The research reveals that the cases of meaning loss, meaning gain, and translation procedures are due to the source language peculiarities and target language peculiarities and not the translators’ latitude. This paper characterizes the modality choices in the translation of business and economic language, which is missing in the literature and gives insights into the role of neutrality in the translation of modal verbs.